2007
DOI: 10.1016/j.janxdis.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-processing sensitivity in social anxiety disorder: Relationship to harm avoidance and diagnostic subtypes

Abstract: Sensory-processing sensitivity is assumed to be a heritable vulnerability factor for shyness. The present study is the first to examine sensory-processing sensitivity among individuals with social anxiety disorder. The results showed that the construct is separate from social anxiety, but it is highly correlated with harm avoidance and agoraphobic avoidance. Individuals with a generalized subtype of social anxiety disorder reported higher levels of sensory-processing sensitivity than individuals with a non-gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 47 publications
4
93
0
3
Order By: Relevance
“…SPS and mental health outcomes.Sensory processing sensitivity has been associated with poor mental health outcomes (Benham, 2006;Evers, Rasche, & Schabracq, 2008;Hofmann & Bitran, 2007;Liss, Mailloux, & Erchull, 2008;Liss, Timmel, Baxley, & Killingsworth, 2005;Meyer, Ajchenbrenner, & Bowles, 2005;Meyer & Carver, 2000;Neal, Edelmann, & Glachan, 2002) and higher levels of stress and ill health (Benham, 2006;Evers et al, 2008). SPS associations with poor mental health outcomes include high scores on self-reported anxiety, but not depression (Neal et al, 2002).…”
Section: Sensory Processing Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…SPS and mental health outcomes.Sensory processing sensitivity has been associated with poor mental health outcomes (Benham, 2006;Evers, Rasche, & Schabracq, 2008;Hofmann & Bitran, 2007;Liss, Mailloux, & Erchull, 2008;Liss, Timmel, Baxley, & Killingsworth, 2005;Meyer, Ajchenbrenner, & Bowles, 2005;Meyer & Carver, 2000;Neal, Edelmann, & Glachan, 2002) and higher levels of stress and ill health (Benham, 2006;Evers et al, 2008). SPS associations with poor mental health outcomes include high scores on self-reported anxiety, but not depression (Neal et al, 2002).…”
Section: Sensory Processing Sensitivitymentioning
confidence: 99%
“…A number of studies have equated SPS with psychopathology, negative mental health outcomes, stress and illness (Benham, 2006;Evers, Rasche, & Schabracq, 2008;Hofmann & Bitran, 2007;Liss, Mailloux, & Erchull, 2008;Liss, Timmel, Baxley, & Killingsworth, 2005;Meyer, Ajchenbrenner, & Bowles, 2005;Meyer & Carver, 2000;Neal, Edelmann, & Glachan, 2002). Importantly, all but one of the studies used self-report, and not clinical, measures, precluding any conclusions about the clinical validity of the findings.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was the avoidance of social situations rather than the anxiety levels that were more strongly associated with tactile sensation abnormalities. Sensory-processing sensitivity, as an individual trait, is thought to manifest itself in the form of avoidance of overstimulation and has been found to be a particular risk factor for social anxiety (Hofmann & Bitran, 2007). Importantly, it suggests those who are socially anxious are predisposed to process information from the environment differently, and tactile stimuli may be one domain in which they are particularly vulnerable (Craske, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…First, highly sensitive individuals, compared with non-HSPs, suffer frequently from stress and anxiety in social and crowded situations (Aron, 1996). Second, they have a lower level of self-acceptance as well as negative attitudes and resistance towards crowded and/or social situations (Liss et al, 2005;Benham, 2006;Hofmann & Bitran, 2007;Aron, 1996). The MBSR program has been shown to be effective in reducing the above-mentioned problems (Miller, Fletcher, & Kabat-Zinn, 1995;Shapiro, Schwartz, & Bonner, 1998;Chang, Palesh, Caldwell, Glasgow, Abramson, Luskin, Gill, Burke, & Koopman, 2004;Shapiro, Astin, Bishop, & Cordova, 2005, Kabat-Zinn, Massion, Kristeller, Peterson, Fletcher, Pbert, Lenderking & Santorelli, 1992, Carson & Langer, 2006, Thompson & Waltz, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies conducted in both clinical and non-clinical groups showed that participating in the MBSR program leads to anxiety reduction (e.g., Miller et al, 1995, Shapiro et al, 1998, Kabat-Zinn et al, 1992. Because HSPs have a higher sensitivity for (social) anxiety (Hofmann & Bitran, 2007;Aron, 1996), it is expected that they could benefit from the MBSR program.…”
Section: Introductionmentioning
confidence: 99%